Psychological, Physiological, and Physical Effects of Resistance Training and Personalized Diet in Celiac Women - Martínez-Rodríguez, Alejandro (2022)
Background: Gluten intolerance is a systemic process of autoimmune nature; it develops in genetically predisposed subjects with gluten ingestion. The only treatment for celiac disease (CD) is a lifelong strict gluten-free diet (GFD). This study was designed to evaluate adherence to a GFD, risk of an eating disorder, and nutritional status in adult CD patients undergoing different interventions. Methods: A total of 28 Spanish women, aged 40 years or more, took part in a randomized controlled trial. Each group received a different intervention: group 1, gluten-free nutrition plan + exercise (GFD + E); group 2, gluten-free nutrition plan (GFD); group 3, celiac controls (NO-GFD); and group 4, non-celiac controls (CONTROL). The training was prescribed by a sport scientist. It was based on resistance training with elastic bands; beforehand a warm-up was performed and the resistance was increased progressively. The variables studied were adherence to the GFD, risk of eating disorders, blood values, and body composition. Results: Celiac women with personalized nutritional planning presented greater adherence to a gluten-free diet (p < 0.001). Regarding leukocytes, significant differences were observed between the GFD and control groups (p = 0.004). Perimeters and folds did not decrease significantly. Conclusion: Women with celiac disease who follow an adapted and personalized diet have a better adherence to a GFD compared to those who follow a non-professional diet, and therefore have a better immune system status (blood leukocytes).